Self-Aligned Polymer Film Patterning on Microstructured Silicon Surfaces - Schutzeichel, Christopher; Kiriy, Nataliya; Kiriy, Anton; Voit, Brigitte (Macromolecular Chemistry and Physics, 2022)
Based on a recently developed selective etching process for silicon samples with buried implants, this work presents a method for utilizing the generated material contrast between silicon and silicon oxide to selectively deposit polymers on the patterned surface. Besides depositing polystyrene selectively on the etched parts via drop-casting and dewetting, polymer chains are selectively grafted to the oxidic surface parts. To this end, the oxide surfaces are selectively modified via functional alkoxysilanes, whereas etched silicon surfaces are unreactive. Using either a two-step or a straight-forward one-step process employing commercially available chemicals, atom transfer radical polymerization (ATRP) initiator functions are attached selectively to the non-etched surface areas, and subsequently used to polymerize either methyl methacrylate (MMA) or N-isopropyl acrylamide (NIPAM) in a controlled surface-initiated activator regenerated by electron transfer (ARGET)-ATRP process. This procedure allows for the further self-aligned functionalization of the micropatterned samples, enabling the production of highly functional, patterned surfaces, potentially suitable for applications in areas such as cell adsorption, microfluidics, or functional microsystems, e.g., MEMS.
CRIS-Team Scopus Importer:2023-03-20
Keywords: controlled polymerization; patterning; self-replication; surface modification